Psychological and sport-specific characteristics of football players - Junge, A.; Dvorak, J.; Graf-Baumann, T.; Chomiak, J.; Peterson, L. (The American Journal of Sports Medicine, 2000)
It is hypothesized that players of different levels of play might differ not only in their football skills but also in their way of playing football and with respect to psychological factors such as concentration, reaction time, or competitive anxiety. The psychological characteristics of a player might influence his way of playing football (in particular with respect to fair play) and also his risk of injury. A group of 588 football players were studied by questionnaire; additionally, reaction time tests were performed. Psychological characteristics were assessed by three established self-evaluation questionnaires: the Athletic Coping Skills Inventory, the State Competitive Anxiety Test, and the State-Trait-Anger-Expression-Inventory. Football-specific characteristics that were investigated included playing experience and positions played, style of play, number of training hours and games, as well as aspects of fair play. Reaction time was tested twice: without the influence of physical exercise and immediately after a 12-minute run. A significant reduction in reaction time was observed after physical exercise. In high-level players, the reaction time immediately after the 12-minute run was significantly shorter than it was in low-level players. The questionnaire answers given regarding fair play clearly indicated that fair play is not paid sufficient respect. The relationship between psychological characteristics and attitudes toward fair play was analyzed and discussed.